2020
DOI: 10.1029/2020gl087563
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Hydraulic Fracturing: A Method to Create Self‐Driven Fractures

Abstract: In this study, we investigate the possibility of using a high-density fluid to induce downward fracture growth in a hydraulic fracturing process. We propose a mathematical model to calculate the minimum amount of a dense fluid required to trigger downward fracture propagation under gravity forces, and we verify the calculated minimum volume of the fluid through numerical simulations. Results show that when the injected fluid exceeds the minimum amount, a steady downward growth of the hydraulic fracture is obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…scalings have been confirmed byMöri et al (2020) andMöri & Lecampion (2021b) using 3D numerical simulations computed with open-source codesSalimzadeh et al 2020) Möri et al (2020). andMöri & Lecampion (2021b) show that for a 3D, constant injection-rate, ascending fracture, the shape of the tip-line depends on a dimensionless ratio that includes viscosity and fracture toughness.…”
mentioning
confidence: 72%
“…scalings have been confirmed byMöri et al (2020) andMöri & Lecampion (2021b) using 3D numerical simulations computed with open-source codesSalimzadeh et al 2020) Möri et al (2020). andMöri & Lecampion (2021b) show that for a 3D, constant injection-rate, ascending fracture, the shape of the tip-line depends on a dimensionless ratio that includes viscosity and fracture toughness.…”
mentioning
confidence: 72%
“…Recent developments in hydrofracturing studies have shown how 3D fracture propagation models that include fluid flow within the fracture are possible to implement, for planar fractures (Salimzadeh et al., 2020; Zia & Lecampion, 2020). Such schemes could be coupled to the model presented here to explain both the spatial and temporal evolution of sills and dykes (Pinel et al., 2017; Salimzadeh et al., 2020; Zia & Lecampion, 2020). It is of note that the simulation time increases rapidly when including this process.…”
Section: Discussionmentioning
confidence: 99%
“…42,[45][46][47][48][49][50][51][52] Unlike the displacement correlation method, the 𝐽-integral is more acceptably extensible to three -dimensional problems, and constitutes an important method in assessing failure in both non-linear and time-dependent materials. 41 The 𝐽-integral has been applied in the hydraulic fracturing context, [53][54][55][56][57][58][59][60] along with alternative energy-based approaches, 61,62 however it has remained elusive whether the aforementioned advantages can be exploited. In particular, these include whether the 𝐽-integral can estimate the stress intensity factor independently to the toughnessviscous propagation regime, and importantly, whether the 𝐽-integral can also be used to extract the propagation velocity of the fracture.…”
Section: Highlightsmentioning
confidence: 99%
“…The J ‐integral has been applied in the hydraulic fracturing context, 53–60 along with alternative energy‐based approaches, 61,62 however it has remained elusive whether the aforementioned advantages can be exploited. In particular, these include whether the J ‐integral can estimate the stress intensity factor independently to the toughness‐viscous propagation regime, and importantly, whether the J ‐integral can also be used to extract the propagation velocity of the fracture.…”
Section: Introductionmentioning
confidence: 99%